Skyline computation of uncertain database: a survey - Ma'aruf, Lawal Mohammed; Ibrahim, Hamidah; Mohd Sani, Nor Fazlida; Yaakob, Razali (School of Computing, UUM College of Arts and Sciences, 2017)
Conducting advance skyline analysis over certain and uncertain databases is still an evolving research area in the field of database, despite several research works that have been conducted in this area. This paper conducts a survey on research issues on computing skyline for uncertain databases, with the view of providing interested researchers with an overview of the most recent research directions in this area. It further suggests possible research direction on skyline processing for uncertain databases. Taxonomy of the existing approaches is also presented.